Molecular regulation of neuronal apoptosis in PC12 cells. - Sridhar, Srikala. (University of Ottawa (Canada), 1997)
In this study apoptosis was induced in neuronal PC12 cells by 2-5 $\mu$M VM26 (teniposide, a known apoptotic inducer) and changes in the expression of genes considered to be involved in apoptosis were examined by RT-PCR. Cell death, DNA fragmentation and morphological changes associated with apoptosis were evident within 8 hours after exposure to VM26 indicating that VM26 is capable of inducing apoptosis. Within 8 hours of VM26 exposure, clusterin (TRPM-2) and IGFBP2 (Insulin-like growth factor binding protein 2) were both upregulated by 3 and 4 fold respectively. Cathepsin B (RSG-2) and RSG-3 (embigin) exhibited marginal changes in expression, only about 1.2 fold, over the 24 hour time course. Finally, IGFBP5 (Insulin-like growth factor binding protein 5) displayed a substantial decrease in expression, with a 4 fold decrease compared to control. Since IGFBPs appear to play a role in apoptosis, the effects of IGF-I treatment on cells undergoing apoptosis was examined. Treatment with IGF-I led to a dose-dependent protective effect on apoptosis induced by VM26. In the presence of 200 ng/ml IGF-I, cell viability was 52.1% at 24 hours compared to non-treated cells, at 35.8% viability. In addition, IGF-I was able to modulate cell viability, in a manner that did not involve induction of proliferation as assessed by cell counts in IGF-I treated and untreated PC12 cells. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.